Constructing a Bicultural Upbringing Environment in Polish-Italian Families - Aneta Wojnarowska (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: The article relates to research in the field of education focusing on family and identity that have gained particular importance in recent years in relation to the increasing number of children brought up in culturally diverse environments and attending Polish kindergartens and schools not only in the territorial border areas. The aim of the article is to show the ways in which Polish-Italian families living in Kraków construct bicultural educational and parenting environments for their children. Research Aim: Research aim was to analyse and interpret the subjective experiences of Polish mothers raising preschool children with partners of Italian nationality. Method: The research project was embedded in a qualitative research orientation, adopting its methodological assumptions. The data was collected during individual, in-depth, semi-structured interviews conducted with 10 women. Results: Following the analysis and interpretation of the women's narratives, four models of upbringing strategies created by Polish-Italian families were proposed to be distinguished. These are: a culturally engaged family, a cosmopolitan (European) family, a culturally passive family, a family of unfulfilled expectations and aspirations. Conclusion: The aim of presenting the diversity of family educational environment of children in Polish-Italian families living in Kraków is to encourage those directly involved in upbringing and education - i.e. teachers or educational authorities - to reflect on the situation of children brought up in binational families for the proper and meaningful design of educational and didactic processes that would take into account these children's family and home experiences, as well as their cognitive and personal potential.